Kommentar zu „Intravenöse Vitamin C-Gabe: 28-Tage-Ergebnis septischer Patienten verschlechtert?“ (Aktuelle Ernährungsmedizin, 2022)
Rarely the results of a study were expected so eagerly as the LOVIT trial, an acronym for “Lessening Organ Dysfunction with Vitamin C” 1. This blinded multicentric randomised trial (RCT) is a well-performed study 1 testing high-dose intravenous vitamin C (IVVC) (50 mg/kg every 6 h for 96hrs). With 872 patients, the trial is the largest so far. The results are sobering, as the patients receiving IVVC had a worse primary composite outcome compared to the placebo group: of note, the different components of the outcome (death or persistent organ dysfunction), did not differ significantly when considered individually 2.